(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of knowledge of the RICE method in treating injuries among Taekwondo athletes in Sarolangun Regency. The athletes’ knowledge level is assessed using several indicators: factual, structural, procedural, and metacognitive. This study was conducted from June 9-16, 2025, in Sarolangun Regency. The literature review emphasized that athletes, including those involved in martial arts disciplines such as taekwondo, need adequate knowledge of first aid. This knowledge should include a thorough understanding of the RICE method, given its vital role as an initial treatment procedure for managing acute injuries. The method used was a descriptive quantitative survey technique. Data were collected through a questionnaire that had been tested for validity, with a total of 15 athletes responding. The results showed that the athletes’ level of knowledge regarding the RICE method in treating injuries was 75.43%, which falls into the "Good" category.